STOCK INVESTMENT ANALYSIS IN PT INDOSAT - Raisa Salsabila; Sara Yulis; Farica Yusrina Lubis; Cut Safani; Alfina Hadi Regita Cahyani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This journal aims to analyze stock investment in PT Indosat, a leading telecommunications company in Indonesia. This research is conducted by analyzing the performance of Indosat's stocks in recent years and evaluating the long-term investment potential of the company. The method used in this research is fundamental analysis, which involves a review of Indosat's financial statements, including income statements, balance sheets, and cash flow statements. Additionally, SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is also utilized to assess Indosat's competitive position in the telecommunications market. The research findings indicate that the performance of PT Indosat's stocks has shown a positive trend in recent years. The company has managed to increase its revenue and net profit while reducing its debt burden. Furthermore, Indosat has taken strategic steps to strengthen its position in the market, such as launching innovative products and services and expanding its geographic reach. However, this research also identifies several challenges faced by Indosat. Intense competition in the telecommunications industry, rapid technological advancements, and complex regulations can impact the company's growth. Therefore, investors need to consider these factors in their investment decision-making. This research provides valuable insights for investors interested in investing in PT Indosat's stocks. By considering the company's financial performance, business strategies, and relevant risk factors, investors can make more informed investment decisions based on in-depth analysis.